Legal Response to Cybercrime in Global and National Dimensions - Dewi Bunga (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
AbstractCybercrime is a serious crime in the era of globalization. This crime employs sophisticated technology and anonymity. It is fast, crosses states’ borders, and has a wide impact. Cybercrime causes both material and immaterial losses. It even threatens world peace and security. The legal issue in this research is to discuss the international response to cybercrime, the substance of the Convention on Cybercrime, Budapest, 23.XI.2001, and Indonesia's position in the Convention on Cybercrime. The international response to cybercrime is done by holding international meetings at the United Nations Congress to discuss efforts to prevent cybercrime. Convention on Cybercrime, is the first provision for regulating cybercrime. The substance of the Convention on Cybercrime consists of material criminal law, procedural law, corporate responsibility, international cooperation and so on. Indonesia's position in the Indonesia Convention on Cybercrime is not to ratify the Convention on Cybercrime, but adopts the provisions of the Convention on Cybercrime on the Law Number 11 of 2008 on Information and Electronic Transactions and the Law Number 19 of 2016 on the Amendment of the Law Number 11 of 2008 on Information and Electronic Transactions. The criminal acts provided for in the Information and Electronic Transaction Law in Indonesia are wider than those stipulated in the Convention on Cybercrime.Respon Hukum terhadap Kejahatan di Dunia Maya dalam Dimensi Global dan NasionalAbstrakKejahatan siber adalah kejahatan serius di era global. Kejahatan ini dilakukan dengan menggunakan teknologi canggih, anonimitas, cepat, lintas batas negara, dan memiliki dampak yang luas. Dampak kejahatan siber tidak hanya menyebabkan kerugian material, tetapi juga kerugian immaterial, bahkan mengancam perdamaian dan keamanan dunia. Isu hukum dalam penelitian ini adalah membahas mengenai respon internasional terhadap kejahatan di dunia maya, substansi Convention on Cybercrime, Budapest, 23.XI.2001, dan posisi Indonesia dalam Convention on Cybercrime. Respon internasional terhadap kejahatan di dunia maya dilakukan dengan mengadakan pertemuan internasional yang ada di Kongres PBB yang membahas mengenai upaya pencegahan kejahatan siber. Convention on Cybercrime, adalah ketentuan pertama untuk mengatur kejahatan siber. Substansi dari Convention on Cybercrime terdiri dari hukum pidana materiil, hukum acara, tanggung jawab korporasi, kerjasama internasional dan sebagainya. Posisi Indonesia dalam Indonesia Convention on Cybercrime adalah tidak meratifikasi Convention on Cybercrime, tetapi mengadopsi ketentuan Convention on Cybercrime pada Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik dan Undang-Undang Nomor 19 Tahun 2016 tentang Perubahan atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Elektronik Transaksi. Tindak pidana yang diatur dalam Undang-Undang tentang Informasi dan Elektronik Transaksi di Indonesia lebih luas daripada yang diatur dalam Convention on Cybercrime.DOI: https://doi.org/10.22304/pjih.v6n1.a4